PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PESERTA DIDIK KELAS V DI SD MUHAMMADIYAH 10 TALLO MAKASSAR - Nurizzati; Aliem Bahri; Sri Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the critical thinking skills of fifth-grade students at SD Muhammadiyah 10 Tallo Makassar through the implementation of the Problem Based Learning (PBL) model. This research employed Classroom Action Research (CAR) consisting of two cycles, each including planning, implementation, observation, and reflection stages. The subjects were 22 fifth-grade students. Data were collected through observation sheets and critical thinking tests. The results showed that in Cycle I, the learning mastery reached 68% (15 students), while in Cycle II it increased to 90% (20 students). Students’ learning activities also improved significantly, especially in analyzing problems, expressing arguments, and drawing logical conclusions. The findings indicate that the Problem Based Learning model effectively enhances students’ critical thinking skills in elementary school settings.